Examining the Intersection of Race, Gender, Class, and Age on Post-Secondary Education and Career Trajectories of Refugees - Bajwa, Jaswant Kaur; Abai, Mulugeta; Kidd, Sean; Couto, Sidonia; Akbari-Dibavar, Aytak; McKenzie, Kwame (Refuge, 2018)
This study examines the role of demographics on education and career trajectories of refugees’ in Canada from an intersectional perspective. It implemented a 14-week unique educational program that was completed by a total of 41 refugees’, over two cohorts with the goal to overcome barriers, bridge gaps and facilitate their transition into higher education. The data collected using semi-structured interview guide was analyzed using a constant comparative method. The findings suggest that a supportive educational model that promotes safety, sense of belonging and empowerment are critical to combat the structural racism, sexism and other discriminatory factors in accessing higher education.